Pengaruh Suhu Pemanggangan Terhadap Kualitas Fisik dan Daya Terima Kue Biji Ketapang - Hidayat, Teddi; Kandriasari, Annis; Alsuhendra, Alsuhendra (Peneliti.net, 2024)
This study was conducted to determine the effect of baking treatment with temperatures of 1300C, 1400C, and 1500C with the same time of 35 minutes, on making ketapang seed cakes on physical quality and acceptability for aspects of color, sweetness, savory taste, baking aroma, coconut aroma, texture and brittleness. Based on the results of statistical hypothesis tests using the Friedman test showed that there was an influence of baking temperature on aspects of color, sweetness, texture and brittleness which resulted in the 1300C temperature treatment ketapang seed cake most preferred by the panelists, and there was no influence of baking temperature on aspects of savory taste, baking aroma and coconut aroma followed by Tuckey's test so as to produce ketapang seed cake temperature treatment of 1300C and 1400C which was most preferred by the panelists. The results of the statistical hypothesis test of physical quality tests using the Anova test showed that the hardness aspect had a real influence or difference which was continued with the Duncan Multiple Range Test (DMRT) test on ketapang seed cake, resulting in ketapang seed cake temperature treatment of 1500C and fried products (control) that were most significantly different, and in the aspect of development there was no influence of roast and fried temperature treatment on ketapang seed cake products. The conclusion of this study is that ketapang seed cake with a temperature treatment of 1300C is the most preferred and recommended to be developed as a traditional cake modification product.